Answer:
The zeroes in this equation are -5, -4, and 5
Step-by-step explanation:
In order to find these, you need to factor by splitting. For this, we separate out the two halves of the equation and pull out the greatest common factor of each. Let's start with the front end.
r^3 + 4r^2
r^2(r + 4)
Now the second half.
-25r - 100
-25(r + 4)
Since what is left in the parenthesis are exactly the same, we can use that parenthesis next to one with what we pulled out.
(r^2 - 25)(r + 4)
And we can further factor the first parenthesis using the difference of two squares
(r^2 - 25)(r + 4)
(r + 5)(r - 5)(r + 4)
Now that we are fully factored, set each parenthesis equal to 0 and solve for x.
r + 5 = 0
r = -5
r - 5 = 0
r = 5
r + 4 = 0
r = -4
Add all the marbles up: 6 + 14 + 7 = 27 marbles
There are 6 yellow marbles and 14 red marbles. 6 + 14 = 20
The probability of selecting a red/yellow marble is a 20 out of 27 chance.
Answer:
x = -3
y = -8
Step-by-step explanation:
2y = x - 13
3x = y - 1; let y = 3x + 1
substitute to solve for 'x':
2(3x + 1) = x - 13
6x + 2 = x - 13
5x + 2 = -13
5x = -15
x = -3
solve for 'y':
3(-3) = y - 1
-9 = y - 1
-8 = y
A function assigns the values. The function of the graph g(x) is 3(2ˣ).
<h3>What is a Function?</h3>
A function assigns the value of each element of one set to the other specific element of another set.
Given the function of the graph is f(x)=3(2ˣ)-3, which is needed to be transformed to g(x), since g(x) is the function of f(x) transformed 3 units upwards therefore, the function of g(x) can be written as,
g(x) = f(x) + 3
g(x) = 3(2ˣ)-3+3
g(x) = 3(2ˣ)
Hence, the function of the graph g(x) is 3(2ˣ).
Learn more about Function:
brainly.com/question/5245372
#SPJ1
Answer:
B-log(x-4)
Step-by-step explanation:
Have a nice day lol i just know things